Status of Peary Caribou and Muskox Populations on Bathurst Island, N.W.T., August 1981 - Ferguson, Michael A.D. (ARCTIC, 1987)
An aerial survey of Bathurst Island, Northwest Territories, Canada, was conducted 10-13 August 1981 to determine if Peary caribou (Rangifer tarandus pearyi) and muskoxen (Ovibos moschatus) had recovered since die-offs in the early 1970s. Sampling intensity was 26%, except for 74% over Polar Bear Pass on central Bathurst Island. Populations of 289 Peary caribou and 208 muskoxen were estimated. The proportion of calves among classified animals was 19% for caribou and 16% for muskoxen. Caribou were concentrated on northern Bathurst, preferring elevations 151-300 m above sea level (asl). Muskoxen were concentrated in southern and central Bathurst Island, preferring elevations below 150 m asl. Spatial separation of the two species during the survey suggested little or no range overlap during late summer. Calf production and/or summer survival in 1981 was significantly greater than in 1974. The 1981 caribou and muskox estimates were only slightly greater than in August 1974. Thus the populations estimated in 1981 showed no marked overall recovery since 1974. Prohibition of harvesting of both species should continue on Bathurst Island. An "extensive-then-intensive" survey design is recommended for future work, based on statistical problems associated with the 1981 and previous surveys.Key words: Northwest Territories, Peary caribou, muskoxen, population status, distribution, management Du 10 au 13 août 1981 on a effectué un relevé aérien de l'île de Bathurst, dans les Territoires du Nord-Ouest au Canada pour déterminer si la population du caribou de Peary (Rangifer tarandus pearyi) et celle du bœuf musqué (Ovibos moschatus) s'étaient remises de la dévastation du début des années 1970. L’intensité de I'échantillonnage était de 26%, sauf dans le Polar Bear Pass au centre de l'île de Bathurst où elle était de 74%. On a évalué les populations à 289 caribous de Peary et à 208 bœufs musqués. La proportion de veaux parmi les animaux qui ont été classifiés était de 19% pour les caribous et de 16% pour les boeufs musqués. Les ...